Fast and reversible bidirectional photomechanical response displayed by a flexible polycrystalline aggregate of a hydrazone. Issue 41 (31st August 2022) - Gupta, Poonam; Allu, Suryanarayana; Hazarika, Pragyan J.; Ray, Nisha R.; Nangia, Ashwini K.; Nath, Naba K.
Abstract : In this study, a typical laboratory experiment was carried out to isolate the flat strips of a flexible polycrystalline aggregate of a hydrazone derivative. Abstract : In this study, a typical laboratory experiment was carried out to isolate the flat strips of a flexible polycrystalline aggregate of a hydrazone derivative. Due to the photoswitching ability of hydrazones, the material displays fast, reversible, and bidirectional photomechanical motion, unlike single crystals of the parent compound.